Recognizing Research Competence and Interest as Basis for Faculty Development Initiatives - Alumbro, Edita C.; Cuadra, Lijueraj J.; Sapan, Mary Jean M. (JPAIR Institutional Research, 2015)
University faculty members were the primary actors in the research production system. The study aimed to ascertain the level of competence of the College of Education (CE) faculty members in conducting research activities. The data were gathered through survey questionnaires and coded in Microsoft Excel. Frequencies and percentages were used in interpreting the data collected. It was revealed that most faculty members were either college or master’s degree holders. Majority of them have not conducted research studies in the last 15 years. Most faculty members carried 21-25 units per semester teaching load. The study concludes that they indicated a fair level of competence in conducting research. Their interest towards research activities exhibited a fair interest which was a positive attitude. They have also indicated high interest in professional development activities, yet they signified a relatively low interest in conducting research without funds and/ or research assistant. Overloaded-teaching units deprived them to their research responsibilities. Therefore, VSU should implement the 15-units-per-semester maximum teaching load. Moreover, faculty members must be encouraged to pursue advanced education. The level of competence in conducting research could be improved if appropriate qualifications and funds were met.